Pengaruh beban kerja, work life balance, kompetensi dan kepuasan kerja terhadap kinerja account representative dengan dukungan sosial sebagai variabel moderating - Hidhayati, Annisa Tri; Hayat, Atma; Yuliani, Rahma (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study focuses on the objective to analyze whether workload, work-life balance, competence and job satisfaction can affect the performance of Account Representatives moderated by social support. Quantitative research is used as an approach in this study. The population used as the object of research is all ARs who work at KPP Pratama Banjarmasin, KPP Pratama Tanjung and KPP Madya Banjarmasin. The sample was selected using purposive sampling method and obtained 67 samples and observation data based on certain criteria. The analytical tool used is PLS-SEM (Partial Least Square Structural Equation Modeling) with the Two-Stage Approach method. The results of this study indicate that workload, work-life balance affect the performance of Account Representatives. While competence and job satisfaction have no effect on Account Representative performance. Social support cannot moderate the influence between workload, work-life balance, competence and job satisfaction on Account Representative performance.